Shikonin combined with methotrexate regulate macrophage polarization to treat psoriasis. Issue 4 (1st April 2022) - Tao, Tingjun; Chen, Yan; Lai, Bochen; Wang, Jinhua; Wang, Weiliang; Xiao, Weimian; Cha, Xushan
ABSTRACT: This study aimed to investigate whether shikonin combined with methotrexate could inhibit psoriasis progression by regulating the polarization of macrophages through in vivo and in vitro experiments. Imiquimod was administrated to the exposed skin of BALB/c mice, and shikonin and methotrexate suspension were also given by gavage. The erythema, scales and thickness were scored for mice lesions in each group, and the total score was obtained by adding the above three scores, and calculated as psoriasis area and severity index (PASI) score. The skin lesion tissue from mice was isolated and used for hematoxylin-eosin staining and immunohistochemistry assay. Drug-containing serum was prepared and administrated into mouse macrophage RAW264.7 cells, followed by simulation of LPS. The levels of tumor necrosis factor-α (TNF-α), Interleukin (IL)-1β, and IL-6 in cell supernatant were assessed using ELISA Kits and real-time PCR. In imiquimod-induced psoriasis mice, shikonin combined with methotrexate exerted protective effects by reducing erythema and PASI scores, decreasing backer score and epidermal thickness, and particularly regulating macrophage polarization. In LPS-stimulated RAW264.7 cells, shikonin combined with methotrexate regulated M1/M2 polarization and altered the levels of M1 markers. Shikonin combined with methotrexate inhibit psoriasis progression by regulating the polarization of macrophages, which may be useful in the treatment of psoriasis. Graphical Abstract: uf0001